A Rare Nonhepatocytic Primary Liver Neoplasm with an Unusual Presentation: Ossifying Malignant Mixed Epithelial and Stromal Tumor - Venus, Albina; Mehta, Sangita Sharma; Natarajan, Sumathi (Indian Journal of Medical and Paediatric Oncology, 2018)
We present a case of a rare liver neoplasm – Ossifyimg malignant mixed epithelial and stromal tumor. This entity has well-delineated morphological and immunohistochemical features, and so can be easily diagnosed, even with core biopsy tissue. Our patient was a middle-aged male, which is unheard of in the literature of this disease. He had a bad recurrence of the disease after surgical removal of the tumor, unlike the previously reported cases with the same diagnosis, where the patients lived for almost a decade after surgery without recurrence. This neoplasticdisease can thus take a destructive course, and a change in treatment methods such as neoadjuvant or adjuvant chemotherapy should be thought of, to make it more beneficial and effective.
Keywords: Adenocarcinomatous; mixed; nonhepatocytic; ossifying; primary; sarcomatous